Herbivory habits of beef cows grazing native range infested by sericea lespedeza - Preedy, Garrett William (Kansas State University, 2013)
Our objective was to determine the effects of supplemental corn steep liquor (CSL) on voluntary selection of sericea lespedeza (SL) by beef cows grazing native tallgrass range. Dietary botanical composition of cows (n = 145; initial BW = 579 ± 91 kg) was evaluated during a 150-d grazing period (5/1 to 10/1). Native pastures (n = 9; 50 ± 17 ha) infested by SL (average SL biomass = 37% of total forage biomass) were assigned randomly to 1 of 2 treatments: grazing by unsupplemented cows or grazing by cows supplemented with CSL (1.79 kg DM • cow-1 • d-1; 45% DM, 34% CP). Cows were assigned randomly to treatment and pasture (stocking rate = 0.5 ha/AUM). Concentration and protein-binding capacity of condensed tannins (CT) in SL were measured monthly. Fecal samples were collected from each cow on 6/1, 7/1, 8/1, 9/1, and 10/1. Herbivory of SL was estimated along line transects in October. Plant fragments in fecal samples were quantified via a microhistological technique; fragment prevalence in fecal material was assumed to equal botanical composition of the diet. Concentration and protein-binding capacity of CT in SL were greatest (P < 0.01) on 8/1 and 9/1, respectively. The proportion of individual SL plants showing evidence of herbivory tended to be greater (P = 0.09) on pastures grazed by supplemented cows compared to pastures grazed by unsupplemented cows (94 vs. 80% of SL stems, respectively). Prevalence of SL in beef cow diets was influenced (P < 0.01) by CSL supplementation and by month. Prevalence of SL in beef cow diets was not different (P ≥ 0.35) between treatments when concentration and protein-binding capacity of CT were relatively low (6/1, 7/1, and 10/1). In contrast, supplemented cows selected more (P < 0.01) SL than unsupplemented cows when concentration and protein-binding capacity of CT were greatest (8/1 and 9/1). We interpreted these data to suggest that voluntary selection of SL by beef cows was inversely related to concentration of CT; moreover, supplemental CSL stimulated voluntary selection of SL during periods of high CT concentration. Supplemental CSL did not influence selection of other plant species that were monitored.
Keywords: Condensed tannins; Diet selection; Lespedeza cuneata; Animal Sciences (0475)